Optimizing the Ion-Optical Design of a Portable Static Mass Spectrometer for Medical Diagnostics - Antonov, A. S.; Aruev, N. N.; Kuleshov, D. O.; Sachenko, V. D. (Journal of analytical chemistry (New York, N.Y.), 2023)
We propose the design of a compact Mattauch–Herzog ion-optical system featuring a double-focusing static mass spectrometer with a cylindrical electrostatic deflector. This system offers second-order angle focusing and first-order energy focusing along the focal line. The collimating system ensures the optimal vertical acceptance of the mass analyzer and maximum ion transmission within the working mass range. The described ion-optical system serves as a foundation for small-sized mass spectrometers, weighing up to ~50 kg, including turbo-molecular and foreline pumps, while maintaining high analytical performance.